ANALISIS KUALITAS SANITASI PENYIMPANAN BAHAN HEWANI UNTUK MENU ALACARTE APPETIZER DI HOTEL FP SURABAYA - Rahayuningsih, Rizqi Utami; Ita Fatkhur Romadhoni; Any Sutiadiningsih; Lucia Tri Pangesthi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to determine: 1). Animal ingredient storage procedures applied at the FP Surabaya Hotel 2). Implementation of sanitation standards in storing animal ingredients used for the ala carte appetizer menu at the FP Surabaya Hotel 3). Employee understanding of the sanitation standards for storing animal ingredients for the ala carte appetizer menu at the FP Surabaya Hotel 4.) The quality of animal ingredients stored with different methods before being used for the ala carte appetizer menu. This type of research is quantitative research, with a descriptive method. The data used are questionnaire data obtained from respondents through distributing questionnaires to 10 respondents (Chef De Partie, Store Keeper, Casual). The results of the study show that 1). Based on the results of interviews with Chef de Partie and store keeper of the FP Surabaya Hotel, this hotel has implemented standard operating procedures in storing animal food ingredients for the à la carte appetizer menu. 2). Based on the results of the questionnaire with a percentage of 95.28%, it can be concluded that the implementation of sanitation for storing animal ingredients in the kitchen of the FP Surabaya Hotel is classified as very good. 3). Hotel FP Surabaya employees' understanding of sanitation and storage of animal products is considered very good, with an average score of 96.15%. 4). The quality of the animal products stored in the three a la carte appetizer menus remains high, with the highest score being for the Grilled Chicken Caesar Salad (72.14%) and the lowest for the Norwegian Smoked Salmon (67.14%). Salmon's more temperature-sensitive storage and packaging quality are believed to be the causes of the quality decline.